CREATIVE ECONOMY: KEY TO DEVELOPMENT IN MARKET AND MARKETING ASPECTS - Loso Judijanto; Urika; Muh Afief Mubayyin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The creative economy is a form of development of the economic concept, but with the addition of creativity. However, creativity is not only limited to production activities, but also includes how raw materials are used and technological innovations in them. Today, understanding market aspects and designing the right marketing strategy is the main key to surviving and developing in business. Market and marketing aspects play an important role in business feasibility studies. Market aspects refer to various factors that influence the dynamics and characteristics of a market. It covers everything from consumer behavior, buyer preferences, competition between brands, to external factors such as government regulations and industry trends. In a business feasibility study, market aspects are aspects related to market conditions in the industrial sector run by a business. The market aspects analyzed will usually include several main things, namely market demand for the product to be sold, the level of competition and competitors' strategies in marketing the product, and market segmentation. The market and marketing aspects in a business feasibility study are key factors that are very important in determining the success of a business.